Can Social Media Maximize Students’ Learning Experience in Translation Class? - Lutviana, Rizky -; Mafulah, siti (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Teaching translation based on practical syllabus emphasize on the much portion on practice in translating text. This study aimed at describing the use of social media (WhatsApp) in translation class as the extension activity to support the classroom learning that is limited by time. The teaching method used was discussion that was done through WA. Each student translated 1 sentence of text then it must be reviewed by three students and lecturer. Questionnaire and test were used to measure students’ achievement and attitude toward the technique. It is found that students’ active participation in discussion improved and 75% students explained that they enjoyed learning translation using social media. It is suggested that the instructor manage the task in a way that it is incorporate with the feature of social media itself.